GREEN CONCEPT IN BUILDING CONSTRUCTION - George Ofori (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Buildings have a major, wide ranging impact on the environment. The features which a building must have in order to be described as ‘green’ or ‘sustainable’ are now well known. Whereas a wholly sustainable building cannot be attained, there is need for action to minimise the adverse impacts of buildings. This contributes to the attainment of sustainable development. In most countries, some efforts are being made by governments, professional institutions and companies to realise sustainable buildings. However, it is evident that much more needs to be done. The effort to attain sustainable buildings has several drivers, including mandatory legal requirements, incentives, benchmarking and labelling schemes, and action by professional institutions. It is suggested here that focus should be on the responsibility of the individual practitioner to work towards the design or construction of sustainable buildings in the normal course of the practitioner’s work. This responsibility is considered from the perspective of the ethics and professionalism of such a practitioner. The roles of various parties in setting out and strengthening this responsibility are discussed.